Effect of formalin preservation on studies on morphology and condition factor of the freshwater shark Wallago attu (Bloch and Schneider, 1801) using truss network system - Kumar, Graish; Bano, Farah; Serajuddin, Mohammad (Indian Journal of Fisheries, 2021)
The study was aimed to evaluate the effect of formalin preservatiion on the shape, size and condition factor of the freshwater silurid catfish Wallago attu (Bloch and Schneider, 1801) using length-weight relationship (LWR), condition factor and truss analysis. A total of 50 specimens of the fish were procured from the river Ganga at Kanpur region. The fresh and formalin preserved fish were measured for total length, standard length and body weight. Results of LWR revealed that the fresh and preserved fish followed different growth pattern and cube law. High values of r2 were obtained for the relationship between length and weight of the fish before and after preservation of the fish in formalin. Decrease in length and an increase in weight was observed in the preserved specimens of the fish due to the effect of formalin but were not statistically significant. The mean condition factor (K) showed significant (p<0.05) change in the fish after preservation. The univariate and multivariate analysis of truss measurements, two partially overlapping different convex hulls of the scatter plot of PC1 on PC2 and canonical discriminant functions showed highly significant morphometric heterogeneity between the specimens of fresh and preserved fish. The results of the present study suggest that fresh specimens of the fish should be used in research studies based on weight and linear body measurements of the fish. Keywords: Condition Factor, Formalin, Length-weight relationship, Truss network system